2022
DOI: 10.1038/s41467-022-29733-3
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor ERR cooperates with the cardiogenic factor GATA4 to orchestrate cardiomyocyte maturation

Abstract: Estrogen-related receptors (ERR) α and γ were shown recently to serve as regulators of cardiac maturation, yet the underlying mechanisms have not been delineated. Herein, we find that ERR signaling is necessary for induction of genes involved in mitochondrial and cardiac-specific contractile processes during human induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) differentiation. Genomic interrogation studies demonstrate that ERRγ occupies many cardiomyocyte enhancers/super-enhancers, often co-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 88 publications
(149 reference statements)
2
34
0
Order By: Relevance
“…To further test whether Esrrg expression is downregulated by LSD1, we made use of H9c2 rat cardiomyocytes, in which ERRγ is functionally involved in the differentiation ( Sakamoto et al, 2022 ). Inhibition of LSD1 in H9c2 cells led to significant upregulation of Esrrg and its downstream Perm1 ( Figure 5—figure supplement 1C ), whereas these genes were downregulated in LSD1-overexpressing H9c2 cells ( Figure 5—figure supplement 1D and E ).…”
Section: Resultsmentioning
confidence: 99%
“…To further test whether Esrrg expression is downregulated by LSD1, we made use of H9c2 rat cardiomyocytes, in which ERRγ is functionally involved in the differentiation ( Sakamoto et al, 2022 ). Inhibition of LSD1 in H9c2 cells led to significant upregulation of Esrrg and its downstream Perm1 ( Figure 5—figure supplement 1C ), whereas these genes were downregulated in LSD1-overexpressing H9c2 cells ( Figure 5—figure supplement 1D and E ).…”
Section: Resultsmentioning
confidence: 99%
“…S8F). ESRRG was known to regulate the expression of cardiac genes via interaction with GATA4 and GATA4-independent metabolic genes 45 . Moreover, we also observed that the motif for TEADs was enriched upon occupancy of GATA4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the regulation of mitochondrial metabolism was shown to be independent from GATA-4 activity. Moreover, PGC-1α activity was recognized for its essential role in the transcriptional regulation by ERRγ ( 86 ).…”
Section: Signaling Pathways Potentially Associated With Human Induced...mentioning
confidence: 99%